Personality characteristics associated with satisfaction with healthcare and the wish to complain - Søren Birkeland; Marie Bismark; Michael J. Barry; Sören Möller (BMC, 2022)
Abstract Background There is increasing evidence that satisfaction with healthcare and complaint rates vary with patients' socio-demographic characteristics. Likewise, patient personality might influence the perception of health care; however, empirical research has been scarce. The aim of this study was to investigate associations between health care user personality and satisfaction with care and urge to complain. Methods This study is a randomized survey among Danish men aged 45 to 70 years (N = 6,756; 30% response rate) with hypothetical vignettes illustrating different courses of healthcare. Assuming they received the care described in vignettes, participants rated their satisfaction and wish to complain on a five-point Likert scale. Information on personality characteristics was obtained through self-reports using the standardized Big Five Inventory-10 (BFI-10). Results In multivariate analyses, we found respondents with higher scores on the agreeableness dimension expressing greater satisfaction with care (Likert difference 0.06, 95% CI 0.04 to 0.07; p < 0.001) and decreased wish to complain (-0.07, 95% CI -0.08 to -0.05; p < 0.001) while high neuroticism scores were associated with less satisfaction (-0.02, 95% CI -0.03 to -0.00, p = 0.012) and an increased wish to complain about healthcare (0.04, 95% CI 0.03 to 0.06, p < 0.001). Interaction analyses could demonstrate no statistically significant interaction between the level of patient involvement in decision making in the scenarios and the effect of personality on respondents' satisfaction and wish to complain. Generally, however, when adjusting for personality, respondents' satisfaction increased (P < 0.001) with greater patient involvement illustrated in case scenarios while the wish to complain decreased (P < 0.001). Conclusion Our findings suggest low agreeableness and high neuroticism scores are associated with lower patient satisfaction with healthcare and increased wish to complain. Irrespective of personality, however, the wish to complain seems responsive to changes in patient involvement, underscoring the importance of inclusive healthcare communication.